Nucleation induced by "Short-Term Pressurization" of an undercooled isotactic polypropylene melt. (December 2016) - Troisi, E.M.; Formenti, S.; Briatico-Vangosa, F.; Cavallo, D.; Peters, G.W.M.
Graphical abstract: Highlights: The effect of pressure pulses on the nucleation process of an iPP melt was studied. An acceleration in crystallization kinetics was observed after the pulses. Enhanced kinetics are explained according to a classical and a "barrier-less" mechanism. The effect is relevant for polymer processing where pressure pulses are common. Abstract: Nucleation of semi-crystalline polymers is very sensitive to perturbations of the melt state. In contrast to the case of flow, the influence of pressure changes on nucleation has been almost neglected so far. In this work we explore the effect of the pressure history on isotactic polypropylene crystallization by applying a brief step-like increase of pressure to the undercooled melt. Using dilatometry and synchrotron X-ray diffraction, an enhancement of crystallization kinetics proportional to the magnitude of the pressure pulse is revealed. This acceleration is linked to an increase of the number of active nuclei after the short term pressurization, as confirmed by ex-situ optical microscopy observations. Up to an order of magnitude increase in nucleation density is found, for pressure pulses around 600–700 bar. The pressure-induced nucleating effect is interpreted in the light of classical nucleation theory; although a non-classical "barrier-less" nucleation mechanism is also envisaged.